(untitled) (Docentes 2.0 Journal, 2020)
Today, society demands that teachers have skills and be digitally literate to exercise a pedagogical practice that supports meaningful learning for 21st century students. Today’s society has had a strong integration of technology in all areas of life, which has allowed man to have access to an extensive amount of information from anywhere in the world. The generations of the 21st century is under the influence of technology, which implies that the training teachers of the 20th century have had to unlearn to enrich their pedagogical practice supported by technology. The present study arose from the need to create classrooms that support the needs of the students, among them, the motivation to learn to learn, such as the effects that technology has on them. It was a quantitative methodological research, the purpose of this was to explain social reality from an objective perspective to create pedagogical plans to improve Technological-Educational instruction. The research was completed on the Technological-Educational Docentes 2.0 platform, with a population of 369 student-teachers. Surveys were carried out to evaluate the knowledge and motivation of the population under study, as well as the revision of classroom planning. Therefore, the results revealed that student-teachers were motivated using technology in the classroom, which drives the strengthening of teachers worldwide supported by Learning and Knowledge Technologies (TAC).